Isolation and identification of allelochemicals that attract the larval parasitoid, Cotesia marginiventris (Cresson), to the microhabitat of one of its hosts - Turlings, Ted; Tumlinson, James H.; Heath, Robert R.; Proveaux, Adron T.; Doolittle, Robert E. (My University, 1991)
Volatiles released from corn seedlings on which beet armyworm larvae were feeding were attractive to females of the parasitoid, Cotesia marginiventris (Cresson), in flight tunnel bioassays. Analyses of the collected volatiles revealed the consistent presence of 11 compounds in significant amounts. They were: (Z)-3-hexenal, (E)-2-hexenal, (Z)-3-hexen-1-ol, (Z)- 3-hexen-1-yl acetate, linalool, (3E)-4,8-dimethyl-1,3,7-nonatriene, indole, α-trans-bergamotene, (E)-β-farnesene, (E)-nerolidol, and (3E,7E)-4,8,12-trimethyl-1, 3,7,ll-tridecatetraene. A synthetic blend of all 11 compounds was slightly less attractive to parasitoid females than an equivalent natural blend. However, preflight experience with the synthetic blend instead of experience with a regular plant-host complex significantly improved the response to the synthetic blend. Our results suggest that C. marginiventris females, in their search for hosts, use a blend of airborne semiochemicals emitted by plants on which their hosts feed. The response to a particular odor blend dramatically increases after a parasitoid experiences it in association with contacting host by-products.
Keywords: Hymenoptera; Braconidae; Cotesia marginiventris; corn; parasitoid; host searching; semiochemicals; synomones